2020
DOI: 10.3389/fmicb.2020.518060
|View full text |Cite
|
Sign up to set email alerts
|

Component Identification and Functional Analysis of Outer Membrane Vesicles Released by Avibacterium paragallinarum

Abstract: Avibacterium paragallinarum, the causative agent of infectious coryza, is known to release outer membrane vesicles (OMVs). In the present study, we investigated the composition, bioactivities, and functional properties of the OMVs of A. paragallinarum. Following extraction and purification, the OMVs were observed to be spherical in shape, with diameters ranging from 20 to 300 nm. The vesicles contained endotoxin as well as genomic DNA. The molecular weights of the OMV-contained protein fragments were mostly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…In our study, Salmonella OMVs promoted the expression of LITAF, IL-6, and iNOS mRNA in HD11 cells ( Figure 3 ), demonstrating that OMVs from chicken S. Typhimurium CVCC542, could promote the activation of chicken antigen-presenting cells HD11, accompanied by the expression of LITAF, IL-6, and iNOS mRNA. Our results were also supported by Mei et al [ 28 ], who observed that the OMVs from the avian bacillus H. paragallinarum could stimulate the expression levels of IL-1β, IL-2, IL-6, IL-10, and iNOS in HD11.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, Salmonella OMVs promoted the expression of LITAF, IL-6, and iNOS mRNA in HD11 cells ( Figure 3 ), demonstrating that OMVs from chicken S. Typhimurium CVCC542, could promote the activation of chicken antigen-presenting cells HD11, accompanied by the expression of LITAF, IL-6, and iNOS mRNA. Our results were also supported by Mei et al [ 28 ], who observed that the OMVs from the avian bacillus H. paragallinarum could stimulate the expression levels of IL-1β, IL-2, IL-6, IL-10, and iNOS in HD11.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Chu et al [ 34 ] showed that incubating HD11 cells with LPS for 24 h significantly increased the phagocytosis of Chlamydia psittaci by macrophages, supporting the notion that LPS is important for the immunostimulatory effect of OMVs. LPS could stimulate the expression of IL-1β, IL-2, IL-6, IL-10, and iNOS in HD11 cells [ 28 ]. We also observed that OMVs from Salmonella entered the cell ( Figure 4 ), and LPS within the cell can activate inflammasomes and cause the production of IL-1β, as reported by Vanaja et al [ 35 ], who observed that E. coli OMVs could carry LPS into the cell to activate the activation of inflammasomes and cause the production of IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Both pathogenic and non-pathogenic gram-negative bacilli secrete vesicles [9]. The fact that bacterial OMVs contain DNA (plasmid, chromosomal, and/or phage-associated) has been admitted [9, 18, 26]. Whether OMVs have complete genome as their parent cells do and if OMVs contain all the genetic information of the bacterial genome are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted as previously discribed [18]. Since the nucleic acid sequence contained in OMVs is a small molecule sequence, and nanopore third-generation sequencing characterized by long-read sequencing, the genome of OMVs was sequenced through second-generation sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation